Artes Grammaticae in frammenti I testi grammaticali latini e bilingui greco-latini su papiro. Edizione commentata - Scappaticcio, Maria Chiara (Sammlung griechischer und lateinischer Grammatiker, 2015)
Artes Grammaticae in frammenti collects and scrutinizes all the known Latin and bilingual (Greek-Latin and Latin-Greek) grammatical texts on papyrus (1st cent. B.C. - VIth cent. A.D) in order to add further tesserae in the mosaic of our knowledge of forms, practices and circulation of Latin grammar and language and of Roman education, especially in the excentric and multilingual areas of the Empire.